The Performance of Concentrically Braced Frames (CBF) in Chevron V Brace and Diagonal Configuration by Considering Various Frame Heights - Panjaitan*, Arief; Hasibuan, Purwandy; Putra, Rudiansyah; Afifuddin, Mochammad; Haiqal, Muhammad; Adian, Fakhran; Naulia, Dwi Putroe; Hazid, Asraf (Aceh International Journal of Science and Technology, 2023)
Concentrically Braced Frame (CBF) is a structural system with high stiffness, so it is recommended to be implemented in earthquake-hazard areas. The stiffness in CBF is contributed by its diagonal component, which is called bracing. Bracing reduces lateral deformation on the frame system because of the earthquake and prevents heavy damage or failure of the structure. So far, several studies have been conducted. However, the effect of the frame height and the bracing configuration on the CBF performance has not yet been clarified. This study analytically investigated several models of CBF in Chevron V Brace and Diagonal configurations. Those models were prepared with different frame heights. The analyses were conducted by employing the cyclic load and considering yield displacement control in each model. The observation was emphasized on the load-displacement hysteresis curve, from which the performance of each model can be revealed. Three parameters of performance are evaluated: strength, stiffness, and dissipation energy. The analysis discovered that the Diagonal CBF performed better than the Chevron V Brace CBF by presenting a larger and more stable hysteresis curve, which is addressed to better energy dissipation. It is also discovered that reducing the frame height is suggested to enhance the CBF performance due to the earthquake.